2014
DOI: 10.1111/ddi.12169
|View full text |Cite
|
Sign up to set email alerts
|

Critically endangered island endemic or peripheral population of a widespread species? Conservation genetics ofKikuchi's gecko and the global challenge of protecting peripheral oceanic island endemic vertebrates

Abstract: Aim To highlight the significant conservation challenge of evaluating peripheral endemic vertebrates in island archipelago systems and to assess empirically the complexities of approaches to conservation genetic studies across political and biogeographic boundaries. To demonstrate the poignant need for international collaboration and coordination when species delimitation problems with high conservation concern involve island endemics with biogeographically peripheral ranges.Location Southeast Asia, Lanyu Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 92 publications
1
23
0
Order By: Relevance
“…A recent phylogeographic (Siler et al 2012c, 2014b) investigation identified eight genetically divergent and geographically structured clades within this Philippine endemic species, confirming previous speculation (Ferner et al 2001, Brown et al 2013) that many Philippine populations constitute a cryptic species complex. In a follow-up study, Siler et al (2014b) recognized Gekko kikuchii as a member of the Gekko mindorensis Complex, with a distribution that included populations from the islands of Luzon (northern Philippines) and Lanyu (Taiwan).…”
Section: Species Accountssupporting
confidence: 81%
“…A recent phylogeographic (Siler et al 2012c, 2014b) investigation identified eight genetically divergent and geographically structured clades within this Philippine endemic species, confirming previous speculation (Ferner et al 2001, Brown et al 2013) that many Philippine populations constitute a cryptic species complex. In a follow-up study, Siler et al (2014b) recognized Gekko kikuchii as a member of the Gekko mindorensis Complex, with a distribution that included populations from the islands of Luzon (northern Philippines) and Lanyu (Taiwan).…”
Section: Species Accountssupporting
confidence: 81%
“…Within the Taiwan-Luzon volcanic belt, long-distance dispersal by skipping the stepping-stone islands in between has been inferred for the Philippine bulbuls (Microscelis amaurotis) from Japan to the Babuyan and Batanes Islands (Oliveros & Moyle, 2010), and for Kikuchi's geckos (Gekko kikuchii) from Luzon to Orchid Island (Siler et al, 2014). However, the prevalence of long-distance dispersal in the Taiwan-Luzon volcanic belt shown herein and in earlier studies requires further examination by comparative analyses of colonization histories and community assemblies across taxonomic groups (Shaw & Gillespie, 2016).…”
Section: Complex Inter-island Colonization and Peripatric Founder Smentioning
confidence: 99%
“…The Kuroshio current is thought to be a strong oceanic mechanism in shaping the distribution of tropical sea grasses (Kuo, Kanamoto, Iizumi, Aioi, & Mukai, 2006) and population genetic structures of skinks in the Ryukyu Archipelago (Kurita & Hikida, 2014). However, the stepping-stone model of colonization in the Taiwan-Luzon volcanic belt has never been rigorously tested using a molecular phylogeographical approach, with the exception of some phylogenetic studies of shrews (Esselstyn & Oliveros, 2010), birds (Oliveros & Moyle, 2010) and geckos (Siler, Oaks, Cobb, Ota, & Brown, 2014), which indicated a direction of colonization from either Northern Taiwan (shrews) and Batanes (birds) or Southern Luzon (geckos). Nevertheless, these earlier studies were limited by representatives from only a few islands across the Taiwan-Luzon volcanic belt to fully address the direction and stepwise pattern of the stepping-stone hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Although this process likely contributed to the development of distinct faunal regions within the Philippines, studies suggest that species diversification patterns in Brachymeles do not follow predicted PAIC-based diversification patterns, with evidence suggesting a number of overseas dispersal events may have also taken place during the radiation of this group throughout the archipelago (Siler et al 2011a). Furthermore, studies on radiations of other Philippine reptiles (Linkem et al 2010(Linkem et al , 2011Siler et al 2010cSiler et al , 2012bSiler et al , 2014Welton et al 2013Welton et al , 2014 have also partially or fully rejected PAIC formation and fragmentation events in the generation and maintenance of species diversity. These studies suggest that additional diversification mechanisms need to be explored to accurately assess and understand the processes that have resulted in the country's diversity of Brachymeles.…”
Section: Introductionmentioning
confidence: 99%